Republic of Belarus : Financial System Stability Assessment; Update, including Report on the Observance of Standards and Codes on Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents an update to the Financial System Stability Assessment (FSAP) on the Republic of Belarus. The paper reveals that the Belarusian financial sector has so far weathered the ongoing turmoil well, reflecting its relatively closed nature and the dominant role of state-owned banks. The regulatory and supervisory framework has improved since the 2004 FSAP. The planned overhaul of government-directed lending mechanisms in the context of the Stand-By Arrangement will help to ensure the long-term viability of the Belarusian banking sector.